Optimization of Microwave-Assisted Hydrodistillation from Indonesian White Pepper (Piper nigrum L.) Essential Oils - Sekar Widyaningrum; Sarifah Nurjanah; Bambang Nurhadi; S. Rosalinda; Rienoviar Rienoviar (The University of Lampung, 2025)
Pepper is one of the agricultural commodities that Indonesia widely exports. Pepper can be processed into various products, including essential oils. Pepper essential oil can be extracted using several methods, including the microwave. This method can speed up the essential oil extraction process. Optimization was carried out using the Box-Behnken design using the three independent parameters: solution ratio, time, and microwave power. The upper and lower limits used for the independent variables are solvent amount of 1,350 mL and 750 mL, time of 90 minutes and 60 minutes, and microwave power of 440 watts and 136 watts. The optimal data generated is treatment with a solvent amount of 1,050 mL, 90 minutes, and 440 watts of power, resulting in validation data of 99.046%. The optimal essential oil treatment gives a specific gravity of 0.8281, a refractive index of 1.4824, solubility in ethanol 1:2, acid number 0.739 mg KOH/g, ester number 19.599 mg KOH/g, and a hue value of 186,38 (green). Oil with optimum treatment also has an IC50 antioxidant activity of 32,919.9 ppm. Keywords: Antioxidant; Extraction; Microwave; Pepper; RSM.